2022
DOI: 10.21608/aps.2022.143040.1092
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pharmaceutical Care Services on Patients with Active Rheumatoid Arthritis: A Randomized Controlled Study

Abstract: The objective of our study was to investigate the impact of pharmaceutical care services on the detection and resolution of drug-related problems (DRPs) in rheumatoid arthritis (RA) patients. It was a randomized controlled study in which 60 eligible patients were recruited and randomly assigned to either an intervention (N = 30) or a control group (N = 30). The intervention group received pharmaceutical care services including management of drug-related problems (DRPs) in addition to standard care. Patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For instance, omega-3 fatty acid attenuated methotrexate-induced nephrotoxicity in a pre-clinical trial ( 32 ), although it is necessary to further validate whether the use of omega-3 fatty acid lowers the risk of ESRD in patients with RA. In this context, it is worthy of note that Hagar et al reported that the introduction of pharmaceutical care services in RA patient treatment protocol effectively resulted in an improvement in the detection and prevention of drug-related problems and showed a significant reduction in Disease Activity Score 28, Health Assessment Questionnaire, and Rheumatoid Arthritis Quality of Life Questionnaire scores ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, omega-3 fatty acid attenuated methotrexate-induced nephrotoxicity in a pre-clinical trial ( 32 ), although it is necessary to further validate whether the use of omega-3 fatty acid lowers the risk of ESRD in patients with RA. In this context, it is worthy of note that Hagar et al reported that the introduction of pharmaceutical care services in RA patient treatment protocol effectively resulted in an improvement in the detection and prevention of drug-related problems and showed a significant reduction in Disease Activity Score 28, Health Assessment Questionnaire, and Rheumatoid Arthritis Quality of Life Questionnaire scores ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, animal studies have shown that metformin can treat inflammatory bowel disease, multiple sclerosis, and autoimmune diseases [ 17 , 18 , 19 ]. Hagar et al [ 20 ] reported that the introduction of pharmaceutical care services in the RA patient treatment protocol effectively resulted in an improvement in the detection and prevention of drug-related problems and showed a significant reduction in disease activity score 28 (DAS28), health assessment questionnaire (HAQ), and RA quality of life (RAQoL) scores. Metformin modulates immune response, autophagy, mitophagy, endoplasmic reticulum (ER) stress, and apoptosis and exerts epigenetic effects [ 21 ].…”
Section: Introductionmentioning
confidence: 99%